JENIS-JENIS BIVALVIA YANG DITEMUKAN DI PERAIRAN PANTAI DESA SULI DAN ERI PULAU AMBON - Salmanu, Sriyanti; Hetharia, Monica; Squarella, Gabriel F (Program Studi Pendidikan Biologi FKIP Unpatti, 2022)
Background: People who live on the coast of Suli Village and Eri Village, Ambon Island also often use bivalves as a source of animal protein food because it tastes good. This habit finally caught the attention of our team to conduct research related to the types of bivalves that exist in the coastal waters of the two villages. And based on the above study, the focus of this research is to identify the types of bivalves that live in the coastal waters of Suli Village and Eri Village, Ambon Island.Research Methods: This research is a quantitative descriptive study and is observational.Results: Based on the results of the research conducted, 8 types of bivalves were found with the details as follows; 6 types of bivalves in the coastal waters of Suli village, namely: Pitar sp, Asaphis violascens, Ruditapes variegatus (GB Sowerby II, 1852), Atactodea striata, Gafarium pectinatum, Calista impar, and 4 types of bivalves in Eri village namely: Hiatula sinensis (Morch, 185 ), Ruditapes variegatus (GB Sowerby II, 1852), Asaphis violascens, Anadara antiquateConclusion: The conclusion that can be drawn is that in the coastal waters of Suli village and Eri village, 8 types of bivalves were found with the details as follows; 6 types of bivalves in the coastal waters of Suli village and 4 types of bivalves in Eri . village